2003
DOI: 10.17221/4102-pse
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selected cultivation on the content of total protein and amino acids in the potato tubers

Abstract: The aim of study was to determine the effect of selected cultivation operations, such as nitrogenous fertilization (60, 90 kg N/ha), row spacing (62, 82, 102 cm), compaction of soil with wheels of farm aggregates (the numbers of passing 2×, 5×, 8×), on quality changes of two potato varieties (Irga and Ekra). The total protein content in the tubers of the tested potato varieties increased with the increase of the nitrogenous fertilization (90 kg N/ha). Genotype features of the tested potato tubers define the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 1 publication
1
12
1
2
Order By: Relevance
“…For all cultivars, total protein concentration in the potato tubers increased with increasing N fertilization rates (Table 5). Mitrus et al (2003) also found an increase in the total protein concentration in the potato tubers with the increase in N fertilization. The protein concentration is an important trait for potato quality.…”
Section: Tuber Dry Matter Yieldmentioning
confidence: 67%
See 1 more Smart Citation
“…For all cultivars, total protein concentration in the potato tubers increased with increasing N fertilization rates (Table 5). Mitrus et al (2003) also found an increase in the total protein concentration in the potato tubers with the increase in N fertilization. The protein concentration is an important trait for potato quality.…”
Section: Tuber Dry Matter Yieldmentioning
confidence: 67%
“…However, potato is important in the human diet, due to the high biological value of the protein and its amino acid composition. Similarly to most quality characteristics, protein concentration can be modified by various factors, such as environment, soil, tillage (Mitrus et al 2003), N fertilizer, and cultivar. For Ágata, Asterix, Atlantic, and Monalisa, tuber pH was not affected by N fertilization rate; average values were 5.51, 5.58, 5.61, and 5.56, respectively.…”
Section: Tuber Dry Matter Yieldmentioning
confidence: 99%
“…Informações sobre a influência de fertilizantes, especificamente do N, sobre a qualidade de tubérculos de batata tem sido obtidas (Mitrus et al, 2003;Goffart et al, 2008), mas os resultados são variáveis, pois a interações entre dose de N, genótipo e condições de crescimento da planta são complexas. Dependendo do ano, dose de N acima da recomendada aumentou o teor de açúcares nos tubérculos de batata (Long et al, 2004) e diminuiu o teor de amido dos tubérculos (Westermann et al, 1994).…”
Section: Introductionunclassified
“…Once more, each cultivar reacted by increasing the protein content after chemical interventions. The significance of the influence of cultivars on the given characteristic was proved by numerous researches (Roztropowicz 1989, Mazurczyk 1994, Mitrus et al 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Once more, each cultivar reacted by increasing the protein content after chemical interventions. The significance of the influence of cultivars on the given characteristic was proved by numerous researches (Roztropowicz 1989, Mazurczyk 1994, Mitrus et al 2003.Weather conditions during the experimental years significantly differentiated the total protein content. The tubers of the mild drought year 2001 gathered the highest content of the given component but a lot less during the humid seasons of vegetation (1999 and 2000).…”
mentioning
confidence: 96%